2020
DOI: 10.3390/ijms21186870
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Pro-Inflammatory Cell-Free MicroRNA Levels in Cerebrospinal Fluid of Premature Infants after Intraventricular Hemorrhage

Abstract: Intraventricular hemorrhage (IVH) represents a high risk of neonatal mortality and later neurodevelopmental impairment in prematurity. IVH is accompanied with inflammation, hemolysis, and extracellular hemoglobin (Hb) oxidation. However, microRNA (miRNA) expression in cerebrospinal fluid (CSF) of preterm infants with IVH has been unknown. Therefore, in the present study, candidate pro-inflammatory cell-free miRNAs were analyzed in CSF samples from 47 preterm infants with grade III or IV IVH vs. clinical contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 51 publications
0
20
1
Order By: Relevance
“…Since miR-155 plays a wide range of regulatory roles in immune cells, it is not surprising that miR-155 is closely involved in the regulation of inflammatory disorders. Recently, it is reported that the hemorrhage-induced cerebrospinal fluid miR-155 is expected to be a biomarker of intraventricular hemorrhage in premature infants as miR-155 effectively reflected inflammatory conditions [ 56 ]. miR-155 is also closely related to the regulation of autoimmune diseases, such as rheumatoid arthritis (RA) [ 57 ], systemic lupus erythematosus (SLE) [ 58 ], and experimental autoimmune encephalomyelitis (EAE) [ 59 ].…”
Section: The Role Of Mir-155 In Sepsismentioning
confidence: 99%
“…Since miR-155 plays a wide range of regulatory roles in immune cells, it is not surprising that miR-155 is closely involved in the regulation of inflammatory disorders. Recently, it is reported that the hemorrhage-induced cerebrospinal fluid miR-155 is expected to be a biomarker of intraventricular hemorrhage in premature infants as miR-155 effectively reflected inflammatory conditions [ 56 ]. miR-155 is also closely related to the regulation of autoimmune diseases, such as rheumatoid arthritis (RA) [ 57 ], systemic lupus erythematosus (SLE) [ 58 ], and experimental autoimmune encephalomyelitis (EAE) [ 59 ].…”
Section: The Role Of Mir-155 In Sepsismentioning
confidence: 99%
“…Subsequently, changes in specific miRs within exosomes in cerebrospinal fluid (CSF) following post-hemorrhagic hydrocephalus have been shown (Spaull et al, 2019). Proinflammatory miRs have also been found to correlate with oxidized hemoglobin metabolites and heme in CSF after intraventricular hemorrhage (Fejes et al, 2020). Additionally, miRs have been widely studied in hypoxic-ischemic encephalopathy in term neonates, in serum, dried blood spots and whole blood, as potential biomarkers of injury severity (Ponnusamy et al, 2016;Wang et al, 2018;Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Mean ± SEM are depicted. Dotted lines depict the mean value of the particular parameter measured in preterm non-IVH control samples [23]. Mean total heme was as low as 0.8 µmol/L and free heme was practically undetectable in the control samples, and this is why the dotted lines cannot be recognized in parts C and D. To compare the data of the two groups, the Mann-Whitney U test or unpaired t-test was applied.…”
Section: Sustained Elevation In Soluble Pro-inflammatory Protein Markers In the Csf After Ivh-ivmentioning
confidence: 99%
“…Increased CSF miR-21 and miR-221 levels have been linked to delayed cerebral ischemia (DCI) in adults with a subarachnoid hemorrhage (SAH) [21], while reduced miR-152 showed anti-inflammatory properties after intracerebral hemorrhage [22]. Our group has recently investigated the expression of some pro-inflammatory miRNAs in CSF specimens of preterm infants after IVH as potential prognostic biomarkers [23].…”
Section: Introductionmentioning
confidence: 99%